Characterizations of microstructure, crystallographic texture and mechanical properties of dissimilar friction stir welding joints for AA2024 and AA7075 under different tool shoulder end profiles. (December 2020) - Zhang, Chenghang; Huang, Guangjie; Cao, Yu; Li, Qilei; Niu, Liqiang; Liu, Qing
Highlights: The microstructure and mechanical properties of the CCS and THS joints were comparatively studied. The width of the TMAZ and the average grain size in the NZ of the CCS joints are smaller than those of the THS joints. Different shear textures are produced in the different positions of the NZ in the CCS and THS joints. The tensile properties of the CCS joints are better than those of the THS joints. The fracture mode of the CCS and THS joints is ductile and brittle failure, respectively. Abstract: In this investigation, the influence of tool shoulder end profiles (concentric circle shoulder-CCS and three-helix shoulder-THS) and rotational speed (ROSP, 800, 1100, 1400 rpm) on microstructure and mechanical performance of the dissimilar FSW AA2024/7075 joints was analyzed in detail. The results indicated that the width of thermos-mechanical affected zone and the average grain size of nugget zone (NZ) in the CCS joints are lower than those in the THS joints, and they all increase with increasing the ROSP. There is a difference on the shear texture types generated in the different positions of the NZ in the CCS and THS joints. Tensile properties of the joints fabricated by employing the CCS tool are excellent compared to the THS tool. The maximum welding efficiency about 90.8 % can be obtained in the CCS joint at 1000 rpm. The fracture mode of the CCS and THS joints is ductile and brittle failure, respectively.